Plasma amyloid‐β oligomerization tendency as a potential predictor for conversion from mild cognitive impairment to Alzheimer's dementia: Findings from the GMCII cohort - Yuhan Xie; Xue Meng; Tao Li; Haifeng Zhang; Yaonan Zheng; SangYun Kim; Chen Zhang; Xin Yu; Huali Wang (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION This study aimed to explore the association between plasma amyloid‐β oligomerization tendency (OAβ) and cognitive performance in Alzheimer's disease (AD) and determine its predictive value for outcomes of mild cognitive impairment (MCI). METHODS Plasma from 727 subjects (286 AD, 260 MCI, and 181 controls) in a case registry was analyzed using the multimer detection system (MDS) to measure plasma OAβ. RESULTS Elevated plasma OAβ was strongly correlated with multidomain cognitive performance in patients with MCI and AD. Patients with MCI with high baseline plasma OAβ demonstrated a higher risk of progressing to dementia (hazard ratio = 1.083, 95% confidence interval [CI] 1.032–1.137). Baseline plasma OAβ effectively predicted MCI‐dementia conversion (area under the curve [AUC] = 0.824, 95% CI 0.752–0.897). DISCUSSION The real‐world findings underscore the clinical relevance of plasma OAβ as a potential predictor for the conversion from mild cognitive impairment (MCI) to dementia. Highlights We recruit study participants of Alzheimer's dementia (AD), mild cognitive impairment (MCI), and cognitively normal controls in a case registry. We use the multimer detection system (MDS) to measure plasma amyloid‐β oligomerization tendency (OAβ). We observe that elevated plasma OAβ strongly correlates with multidomain cognitive performance in patients with MCI and AD. MCI individuals with high baseline plasma OAβ demonstrate a higher risk of progressing to dementia. The real‐world findings underscore the clinical relevance of plasma Oaβ as a potential predictor for the conversion from MCI to dementia.